(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article focuses on creating dictionaries of a new type that would meet the demands of both the scientific community and general public. It also deals with the problem of lexicography of precedent phenomena. The paper investigates the principles of precedent name and statement lexicography proposed by D. Gudkov. Moreover it represents and analyzes the samples of dictionary articles proposed by this scientist. This research studies the precedence category, which should be taken into consideration as a scientific basis while developing both the project “Dictionary of precedent phenomena” in Ukrainian and other samples of lexicographic works, such as “Dictionary of precedent Biblical phenomena”, “Dictionary of folk precedent phenomena”, “Dictionary of ancient mythology and literature precedent phenomena”, “Dictionary of precedent names”, “Dictionary of precedent statements” etc. Precedent phenomena are introduced as nuclear elements of the cultural space, representing the mentality of the national linguistic and cultural community as the result of knowledge and worldview of different generations in a certain language. Such units are the examples of cognitive reality processing, which have significant ties to the fundamental value orientations of some language culture, actualizing culturally relevant information. This paper is focused on the features of selecting the actual material, its systematization, and difficulties, which lexicographers usually face. This article notes that the register of the above mentioned dictionary should contain primarily samples of units that demonstrate the so-called strong precedence, constitute the core of the folk’s cultural memory, preserved in the minds of the most native speaker, and participate in the formation of the language worldview. This research distinguishes the main elements in lexicographic analyzing of precedent phenomena. These elements include the following: 1) the form of verbalization (precedent name; precedent statement; precedent text; precedent situation); 2) the level of precedence (universally precedent; socially precedent; nationally precedent); 3) source of origin. The dictionary article provides compulsive (somewhere even optional!) structural elements represented in the way of encyclopedic information, illustration and certification. This paper also gives the examples of dictionary articles.